Perceptions on The Application of Financial Reports are Very Important for MSMEs - Wahyu Hidayatullah; Imam Maulana Iqbal; Heny Triastuti (Westscience Press, 2023)
The aim of this research is to determine the perception that the application of financial reports is very important for micro, small and medium enterprises (MSMEs) because many MSMEs do not apply financial reports to their businesses. This research method is a descriptive approach. The research results show that MSME players have a poor perception of the application of financial reports because preparing financial reports is considered difficult and takes a long time. They also believe that implementing financial reports is not important to them, and that the most important thing for them is increasing sales revenue. Financial reports are only required for borrowing funds for small and medium enterprises (MSMEs).